Learning disabilities and University: working for integration (Journal of Parents and Teachers, 2013)
The University Pontificia de Comillas training programs for young adults with intellectual disabilities not only benefit the acquisition of the competences needed for supported employment but also promote well-rounded education in all areas of the student´s lives
Keywords: Intellectual disabilities; University; Employment; Supported Employment; Inclusion; Family and disabilities